PERANCANGAN KOMUNIKASI VISUAL SIGN SYSTEM OBJEK WISATA PANTAI GANDORIAH KOTA PARIAMAN - KHAIRUL, Drs. Syafwandi, M.Sn, Ir.Drs. Heldi, M.Si (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of sign systems at Gandoriah Beach as a tourism object is to help the visitors to find an easy direction for the tourists in exploring the tourism sites that they need with a sense of convenient, secure and orderly. Sign systems have to be able to resist corrosive, unbreakable, and high durability to enhance Pariaman’s tourism in order to increase the public service and it also give a contribution to applicate the Gandoriah Beach’s design. Based on the functional perspective, there are 4 functions of sign systems; (1) identification sign, to identify the location, (2) direction sign, to direct the tourists, (3) regulatory sign, appealed tourists to be orderly and regularly, and (4) information sign provides information needed by the visitors. The existence of sign systems are expected to give a contribution to the visitors, so they can feel safe and comfortable as long as they come to Gandoriah Beach. It also becomes the tourism object as place for visitors to get their comfort.Key words; sign system, public service, tourism object.